PENERAPAN APLIKASI SISTEM KEUANGAN DESA SEBAGAI PERWUJUDAN GOOD CORPORATE GOVERNANCE (GCG) DALAM PEMERINTAHAN DESA - BAMBANG DEWANTORO; MEIDA RACHMAWATI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The current regime, is a regime that tries to manage governance as best as possible with various approaches. Good intentions are certainly approached all levels of government administration to the village level. Regional autonomy gives great power to the regions to act and improve. The village law number 6 in 2014 that was present increasingly provided adequate legal facilities for the implementation of these good ideals. On the ethical guidance side, we recognize how the concept of good governance is used as an institutional framework for strengthening village autonomy. The previous fact is that good governance practices in management practice more funds are directed to the central government, not to the public. The purpose of this reflective study is to understand the forms and practices of good governance and practices in managing village funds as seen from the process of transparency, accountability and responsiveness. The author will associate one of the instruments to ensure the three things above go as expected. The instrument is the application of the village financial system. This study uses an interpretive paradigm with a phenomenological approach to explore how the application of the village financial system as a manifestation of the concept of GCG in governance in the management of village funds. This study found that the GCG concept encompasses the intersection between the village financial system and the village information system.